Glycosidically-bound aroma volatile compounds in the skin and pulp of 'Kensington Pride' mango fruit at different stages of maturity - Lalel, H.; Singh, Zora; Tan, S. (2003)
'Kensington Pride' mangoes (Mangifera indica L.) were harvested at the mature green, half ripe and ripe stages to investigate glycosidically-bound aroma volatiles in their skin and pulp. The aglycones extract was obtained by Amberlite XAD-2 adsorption and methanol elution followed by hydrolysis with -glucosidase and hemicellulase. Analysis of aglycones was achieved by using gas chromatography coupled with a mass selective detector. The composition and concentrations of glycosidically-bound aroma compounds of the 'Kensington Pride' mango were strongly influenced by fruit part and maturity stages. Ninety-two aglycones were detected in the pulp and 85 aglycones were present in the skin. Glycosidically-bound aroma volatile compounds produced via aromatic amino acid metabolites were the most abundant class of compounds found in the skin, whilst in the pulp, terpenes were found to be the most abundant compounds, accounting for 41.18 and 38.04% of the total number of compounds in skin and pulp, respectively. Glycosidically-bound aroma volatile compounds produced via carbohydrate metabolism and terpenes were higher in the skin than in the pulp of mangoes at all maturity stages. Some other compounds, including glycosidically-bound aroma volatile compounds produced via lipid, aromatic amino acid and carotenoid metabolism were higher in the skin than in the pulp only at the mature green and half ripe stage, whilst glycosidically-bound acids were higher in the skin than in the pulp at the half ripe and ripe stage. Most of the glycosidically-bound aroma compounds increased in the pulp as maturity progressed. Amongst all glycosidically-bound aroma compounds only terpenes may contribute to the aroma of fresh ripe 'Kensington Pride' mangoes.